2017
DOI: 10.3390/ijerph14060653
|View full text |Cite
|
Sign up to set email alerts
|

Association between Six CETP Polymorphisms and Metabolic Syndrome in Uyghur Adults from Xinjiang, China

Abstract: Objective: To explore the association between CETP gene polymorphisms and metabolic syndrome (MS), as well as the relationship between the CETP gene polymorphisms and each component of MS. Methods: A total of 571 individuals which were randomly selected from 5692 Uyghur adults were subdivided into two groups, including 280 patients with MS and 291 control subjects, using the group-matching method after matching for gender. We detected CETP polymorphisms (rs5882, rs1800775, rs3764261, rs12149545, rs711752, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Though the CETP variant did not survive conservative Bonferroni correction, we observed a strong association of rs708272 with increased HDL (ß = 4.03, p = 5.63 × 10 −40 ) and decreased TRG (ß = −2.43, p = 9.60 × 10 −5 ) levels. Consistent to our observations previous literature has shown that some variants in the CETP gene, an essential protein of reverse cholesterol transport process are associated with decreased plasma CETP protein activity and protein levels, culminating in higher concentrations of HDL 95,96 and reduced concentrations of TRG 13 . Similarly, meta-analyses have shown that carriers of the T allele, associated with lower CETP, have higher HDL concentrations than CC homozygotes 97 and thereby showing an inverse association with MetS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Though the CETP variant did not survive conservative Bonferroni correction, we observed a strong association of rs708272 with increased HDL (ß = 4.03, p = 5.63 × 10 −40 ) and decreased TRG (ß = −2.43, p = 9.60 × 10 −5 ) levels. Consistent to our observations previous literature has shown that some variants in the CETP gene, an essential protein of reverse cholesterol transport process are associated with decreased plasma CETP protein activity and protein levels, culminating in higher concentrations of HDL 95,96 and reduced concentrations of TRG 13 . Similarly, meta-analyses have shown that carriers of the T allele, associated with lower CETP, have higher HDL concentrations than CC homozygotes 97 and thereby showing an inverse association with MetS.…”
Section: Discussionsupporting
confidence: 93%
“…This has also been observed in the genetic association studies suggesting that genetic effects on lipid levels are more pronounced than for other traits 10 . Most of the genetic association studies for MetS have been conducted in adult population 5,10,11 and are limited by the usage of one-point measurements 7,[12][13][14] . As the prevalence of MetS in children and young adults is increasing 15 , a better understanding of the genetics that underlies MetS throughout childhood and adolescence will provide critical insights into the origin of the disease.…”
mentioning
confidence: 99%
“…Based on genotype CETP −629 C/A gene promoter, it was also found that there was no significant relationship between AA genotypes in both groups (MS obese and non-MS obese) compared to CC genotypes against MS risk. A study by Hou et al found a significant differences involving frequency of genotypic distribution and alleles from rs1800775 (−629C/A), rs3764261, rs12149545, rs711752, and rs708272 between the control group and metabolic syndrome (all p < 0.05) [21]. The study was conducted in a minority adult population in China that included 571 subjects (280 patients and 291 controls).…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted in a minority adult population in China that included 571 subjects (280 patients and 291 controls). Our study did not conduct a separate analysis of the genotypic distribution of AA, CA, and CC, as well as the frequencies of C and A alleles between cases and controls [21]. .08], p = 0.002) ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation